Enhancement of the hypotensive and vasodilator effects of endotoxaemia in conscious rats by the endothelin antagonist, SB 209670. - Gardiner, S. M. (1995)
In conscious, chronically-instrumented rats, the non-selective endothelin antagonist, SB 209670 (10 micrograms kg-1 min-1), caused marked enhancement of the fall in mean arterial blood pressure during infusion of lipopolysaccharide (LPS) for 24 h (LPS alone = -6 +/- 3 mmHg; LPS+SB 209670 = -30 +/- 2 mmHg). This effect was accompanied by a conversion of the mesenteric vasoconstriction to a substantial mesenteric vasodilatation and an augmentation of the hindquarters vasodilatation, seen with LPS alone. Notably, the marked renal hyperaemic vasodilatation during LPS infusion was not affected significantly by SB 209670. These results indicate that endothelin, directly and/or indirectly, plays a pivotal role in the cardiovascular sequelae of endotoxaemia in conscious rats, and prevents marked hypotension, particularly by opposing mesenteric vasodilatation.